PENGARUH EFEKTIVITAS PENGENDALIAN BIAYA, TINGKAT PERPUTARAN KAS DAN PIUTANG TERHADAP RENTABILITAS EKONOMI PADA KOPERASI PEGAWAI NEGERI KABUPATEN MERANGIN - Eryasi Daryati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study aims to determine the effect of cost control effectiveness, cash and receivable turnover rates on economic profitability in civil servant cooperatives in Merangin Regency for the 2016- 2018 period. The partial test results, the cost control effectiveness variable has a value of tcount <ttable where - 3.146 <-2.045 with a significant level of 0.004 less than 0.05. Partial test results, the variable cash turnover rate has a value of t count> t table where 3,425> 2,045 with a significant value of 0.002 less than 0.05. Partial test results, the variable receivables turnover has a value of t count> t table where 4.374> 2.045 with a significant level of 0.00 <0.05. Simultaneous test results, the variable cost control effectiveness, cash turnover rate and accounts receivable turnover rate has Fcount> Ftable, namely 64.102> 2.93 with a significant level of 0.00 less than 0.05. So it can be concluded from the test results above that the cost control effectiveness variable (X1), the cash turnover rate variable (X2) and the accounts receivable turnover rate variable (X3) simultaneously affect the economic profitability of KPN in Merangin Regency. To find out how much the ability of the independent variables in explaining the dependent variable, this result is supported by the coefficient of determination (R2) of 0.855 or (85.5%), which means that the economic profitability variable can be explained by independent variables (cost control effectiveness, level cash turnover and accounts receivable turnover) was 85.5% while the remaining 14.5% was influenced by other variables not examined.